Analisis pelaksanaan pendidikan pemakai (user education) bagi pemustaka di Perpustakaan Universitas Muhammadiyah Mataram - Laila, Alfaigah Fajriatul; Ningsih, Nurwahyu; Faizah, Wafiq (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
This study aims to analyze the implementation of user education programs at the Library of Universitas Muhammadiyah Mataram. User education plays a vital role in enhancing students' information literacy skills and supporting the optimal use of library services. Employing a descriptive qualitative approach, this research utilized interviews, observations, and document analysis involving librarians and users participating in the user education program. The findings indicate that the implementation of user education at UMMAT Library is primarily conducted in the form of student orientation sessions and is carried out incidentally. The methods used remain conventional, such as lectures and printed brochures, and are not supported by digital learning media. User participation is relatively low, and the program's effectiveness is limited due to the absence of continuity and a lack of institutional policy support. The main obstacles include limited human resources, inadequate training facilities, and the absence of a program evaluation system. This study recommends the integration of user education into the academic curriculum, the development of digital learning modules, the establishment of ongoing training, and cross-unit collaboration within the university to realize a user education program that is adaptive, effective, and relevant to users’ needs.